2010
DOI: 10.1186/1471-2458-10-58
|View full text |Cite
|
Sign up to set email alerts
|

Cluster randomized trial in smoking cessation with intensive advice in diabetic patients in primary care. ITADI Study

Abstract: BackgroundIt is a priority to achieve smoking cessation in diabetic smokers, given that this is a group of patients with elevated cardiovascular risk. Furthermore, tobacco has a multiplying effect on micro and macro vascular complications. Smoking abstinence rates increase as the intensity of the intervention, length of the intervention and number and diversity of contacts with the healthcare professional during the intervention increases. However, there are few published studies about smoking cessation in dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…The design and characteristics of the intensive advice in diabetic patients in primary care (ITADI) study have been previously reported [30]. ITADI was a cluster randomized, controlled and multicenter clinical trial, in which the primary health care team was the unit of randomization.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The design and characteristics of the intensive advice in diabetic patients in primary care (ITADI) study have been previously reported [30]. ITADI was a cluster randomized, controlled and multicenter clinical trial, in which the primary health care team was the unit of randomization.…”
Section: Methodsmentioning
confidence: 99%
“…The phases of the study have been described elsewhere [30]. Briefly, after presenting the project to all potential primary care teams, general practitioners and nurses who wanted to collaborate signed a commitment form.…”
Section: Study Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the main limitations of the study is that we will only include professionals who know how to use computers and E-mail and can assure participation in the study by using it. However we feel confident that an important number of participating professionals will run correctly the program since most of them have previously participated in other complex tobacco studies undertaken in our territory such as the ISTAPS (176 basic care units that worked in 82 Spanish primary care centers; participants: 2,827 smokers aged 14–85 years), ITADI (400 professionals and 1077 diabetic smokers) and BIBE studies (162 pediatric teams from 96 Spanish primary care centers; participants: 1101 child) [12,18,52]. No economic compensation will be offered to sanitary professionals; consequently, those who expect to be reimbursed for this extra activity will be also excluded of the study.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies in our country have used this model among diabetic smokers patients attended in primary care and to confirm smoking abstinence using cooximetry [18] and another where information gathered by cooximetry is the main element to motivate smokers to quit [19]. …”
Section: Introductionmentioning
confidence: 99%